Association between cystatin C and major adverse cardiac events in patients with ischemic heart disease and type 2 diabetes mellitus after acute coronary syndrome - S. A. Serik; T. H. Ovrakh (Zaporožskij Medicinskij Žurnal)
Purpose. To evaluate the level of cystatin C and its association with the risk of developing repeated major adverse cardiac events (MACE) in patients with ischemic heart disease (IHD) and preserved kidney function in combination with type 2 diabetes mellitus (DM) within 12 months after acute coronary syndrome (ACS). Materials and methods. A total of 88 patients, aged 30–75 years, (59 patients with DM and 29 patients without DM) with prior ACS (unstable angina or myocardial infarction) in the previous 4–6 weeks were enrolled. The control group consisted of 15 healthy persons. The follow-up period was 11 months.